What is the role of artificial intelligence in sports? - Dhar, V. (Big data, 2017)
With the rapid advances of artificial intelligence (AI) in perception, machines are able to watch and analyze games at a fine-grained level that is virtually impossible for humans to record and process. Machines can now track players and calculate useful metrics without the need for laborious human labeling.3 They can even estimate the effectiveness of every pass along multiple dimensions, such as the risk-to-potential reward ratio associated with a pass, the "pressure" being applied by the opposing team before the pass, and so on. The machine is also able to infer things, like the intent of each pass, automatically by analyzing the positions and velocities of all players on the field. It can also automatically label such passes as "completed," "intercepted," "scored," etc.